Prognostic Role of the Activated p-AKT Molecule in Various Hematologic Malignancies and Solid Tumors: A Meta-Analysis - Yao, Zhen; Gao, Guangyu; Yang, Jiawen; Long, Yuming; Wang, Zhenzhen; Hu, Wentao; Liu, Yulong (Frontiers in Oncology, 2020)
Cancer is one of the leading causes of human death worldwide. In recent years, many studies have firmly established the causal relationship between oxidative stress and cancer initiation and progression. As a key protein in PI3K/Akt signaling pathway, p-AKT (phosphorylated Akt) participates in the process of oxidative stress and plays a prognostic role in various hematologic tumors and solid tumors. We comprehensively searched PubMed, Embase and Cochrane Library to identify studies published in the last ten years involving cancer patients expressing p-AKT and which reported overall survival during the follow-up period. In this study, a total of 6128 patients were evaluated from 29 enrolled articles, and we concluded that overexpression of p-AKT was closely related with worse overall survival (OS) in cancer patients with a hazard ratio (HR) of 2.33 (95% CI: 1.67‐4.00). Besides, subgroup analysis proved that overexpression of p-AKT was related with worse OS in hematological tumor (HR: 1.64, 95% CI: 1.41‐1.92), and solid tumor (HR: 2.44, 95% CI:1.61‐5.26). High expression of p-AKT is associated with poor prognosis of various hematologic tumors and solid tumors.